Measuring the Economic Returns of Vocational Digital Skills and Their Heterogeneity in the Digital Economy Transformation from Korean Labor Market - Zhang Xuhai; Liu Ziyang; Yu Cheng; Li Fangyu; Gao Liankui; Wu Tianfei (Journal of Exploration of Vocational Education, 2026)
As the South Korean government vigorously promotes the "Digital New Deal," digital skills have surpassed traditional educational attainment to become a core human capital element determining labor market performance. However, existing research largely focuses on general computer literacy, lacking precise measurement of the economic returns to specific vocational digital skills. Based on an extended Mincerian Wage Equation and utilizing micro-data from the Korean Labor and Income Panel Study (KLIPS), this paper empirically analyzes the differentiated impacts of general digital literacy versus specialized vocational digital skills on worker compensation. The results indicate that, after controlling for years of education, work experience, and demographic characteristics, workers possessing specialized digital skills (e.g., data analysis, programming, automation control) enjoy a significant wage premium of approximately 14.2%, far exceeding the 5.8% premium for those with only general digital skills. Further heterogeneity analysis reveals significant structural differences in these returns within the labor market: the return on skills in large Chaebol conglomerates (18.7%) is significantly higher than in Small and Medium-sized Enterprises (SMEs) (9.5%), demonstrating a "skills-scale" complementarity effect. Furthermore, for graduates of Technical and Vocational Education and Training (TVET), acquiring advanced digital skills significantly narrows the income gap with general higher education graduates. This study confirms the economic necessity of the digital transformation of vocational education in the Industry 4.0 era and provides empirical evidence for alleviating labor market polarization in Korea and similar East Asian economies.